UPAYA PERLINDUNGAN HUKUM BAGI PIHAK YANG MENGUASAI OBJEK EKSEKUSI AKIBAT ADANYA PUTUSAN EKSEKUSI - Manab, Abd; Rizki Rachmawati, Ayudya (Program Studi Hukum Keluarga Islam, 2022)
This development in reality ignores the rights of weak communities as has happened in many areas regarding the execution of land that occurred in Meruya, one example, which causes tensions between the community and the government, as a result the tension continues in the case process to the District Court which has not been resolved. Another example is the case of land executions that occurred in the Medan Province Region which continued to the Medan District Court by the plaintiff who was continued to the High Court and finally to the Supreme Court because of the appeal and cassation carried out by the defendant. In order to fulfill debt obligations fairly, it must pay attention to the legal protection obligations for creditors holding mortgage rights. The legal protection provided by Article 56A paragraph (1) of the UUK is stated as stated, namely: